Application of Spectrum Analysis Technology in Music Audio Analysis - Yi Li (Advances in Multimedia)
In order to improve the music analysis technology, this paper studies the music analysis technology combined with the spectrum analysis technology and builds an intelligent audio analysis model. In this paper, the nonlinear theoretical method is adopted, and the motion equation of the audio frequency is obtained through variable processing, so as to obtain the mean square fluctuation of the two sound wave models and then obtain the entanglement and compression. Moreover, this paper introduces the combined mode method to describe the interaction of the two laser fields and atomic matter and verifies that both the differential modes are decoupled from the interaction and only the sum mode participates in the interaction. The experiment verifies that the music audio analysis system based on spectrum analysis technology proposed in this paper can play an important role in music analysis.